Pesantren Hybrid Worldview: Moderatisasi Paradigma Penalaran Keislaman dan Pemenangan Kontestasi Wacana Daring - Mochammad Zaka Ardiansyah (UIN Sunan Ampel Surabaya, 2019)
Until 2016, National Board for Terrorism Prevention (BNPT) indicates that Indonesian pesantren has not been yet spotless from radicalism. On the other hand, discourse contestation in virtual world requires santri and pesantren alumni to convey peaceful messages in an attempt to balance radical discourses. Through this article, the author offers a hybrid worldview, a perspective and curriculum revolution of moderate that encourages santri to preserve the tradition of obedience to kiai. This perspective also encourages students to focus on developing critical reasoning, to have paradigmatic reasoning competencies that are adaptive to the dynamics of current period and tolerant to differences, to be rational and autonomous, and to be selective towards the literature used by of pesantren students. This article recommends coding skills with the R language programming and big data management for santri. This aims to accelerate the growth of the moderate internet portal creators in order to dominate online discourse.